The Relationship between Impulsive Buying Behavior and Personality Traits among Indian Consumers - Tulika Sharma (International Journal of Indian Psychȯlogy, 2022)
The purpose of this study is to explore the relationship between personality traits and consumer’s impulsive buying behavior. The total sample size was 61, comprising of males and females. Out of them (n=22) were males and (n=39) were females. The age range of the participants was 19 years -35 years. The sample of   participants are from different regions of India. The instruments used to administer this study were “Ten Item Personality Inventory” developed by Gosling, Rentrfrow, and Swann in 2003 and “Impulsive Buying Scale” was used in this study developed by Rook and Fisher (1995). This study was based on a quantitative, correlational research design and conducted during COVID-19. The study revealed that there exists significant relationship between personality traits and consumer’s impulsive buying behavior of India.